Gamification in Ethnophysics and Its Impact on Digital Learning: A Systematic Literature Review - Riswanto, Riswanto; Alarifin, Dedy Hidayatullah; Hidayat, Arif (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
As digital learning environments evolve, there is a growing demand for culturally relevant and engaging instructional strategies. Gamification has emerged as a powerful tool to enhance student motivation and participation, while Ethnophysics offers a framework for integrating indigenous knowledge into science education. However, the combined application of these approaches remains underexplored. This study aims to investigate the potential integration of gamification elements within Ethnophysics to improve digital learning, with a focus on identifying key trends, conceptual gaps, and implementation challenges. A systematic literature review was conducted following PRISMA guidelines, focusing on Scopus-indexed publications. VOSviewer was employed to map research patterns, dominant themes, and conceptual gaps. The findings highlight four key gamification elements leaderboards, simulations, escape rooms, and interactive assessments that, when integrated with immersive technologies such as virtual reality (VR) and augmented reality (AR), significantly improve students’ conceptual understanding, digital literacy, and self-regulated learning. These elements also align with traditional cultural practices, making physics education more meaningful and contextually relevant. Despite these advantages, challenges persist, including the absence of a standardized gamified Ethnophysics model and limited access to advanced technologies in under-resourced settings. To address these issues, the study proposes a conceptual framework emphasizing inclusivity, cultural relevance, and affordability, offering practical guidance for researchers and educators seeking to implement culturally responsive digital learning strategies.